2009
DOI: 10.1128/cvi.00036-09
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance of a Novel Herpes Simplex Virus Type 2-Specific Enzyme-Linked Immunosorbent Assay Using a Targeted Chain Oligopeptide, Peptide 55

Abstract: Herpes simplex virus (HSV) glycoprotein G (gG2) has been used as the basis of many serological assays for the detection of HSV type 2 (HSV-2)-specific antibodies. In the present study, an enzyme-linked immunosorbent assay (ELISA), the Pathozyme Viro HSV-2 immunoglobulin G (IgG) ELISA (Omega Diagnostics, Alva, United Kingdom), based on an immunodominant epitope of gG2 presented in a branched-chain format (peptide 55), was compared with two commercially available gG2-specific assays, the Bioelisa HSV-2 IgG assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…However, specificity is still a problem with current tests, especially in African sera . Previous studies have indicated that peptides corresponding to partial sequences of certain viral proteins of HSV-2 may be useful in HSV-2 type-specific detection, as these peptides may represent some HSV-2 type-specific epitopes . However, for an unambiguous result in diagnostics, it would be desirable to identify or design epitopes with an even higher sensitivity and specificity.…”
mentioning
confidence: 99%
“…However, specificity is still a problem with current tests, especially in African sera . Previous studies have indicated that peptides corresponding to partial sequences of certain viral proteins of HSV-2 may be useful in HSV-2 type-specific detection, as these peptides may represent some HSV-2 type-specific epitopes . However, for an unambiguous result in diagnostics, it would be desirable to identify or design epitopes with an even higher sensitivity and specificity.…”
mentioning
confidence: 99%
“…3D cell culture model was developed by spheroid generation by transferring the hydrogel printed on a 3D printer by plating 1 × 10 4 cells/well. The preparation of hydrogel using acrylamide and bis‐acrylamide was followed according to the standard protocol 49‐51 . Briefly, the acrylamide and bis‐acrylamide were taken from a stock of 29:1 (wt%) acrylamide:bis‐acrylamide mixture and diluted (1:1) with water or glycerol, tartrazine (≈0.027 wt%), and 0.1 wt% lithium phenyl‐2,4,6 trimethyl benzoyl phosphinate (LAP).…”
Section: Methodsmentioning
confidence: 99%
“…The range of volume used in our experiments is similar to the sample volume used in other techniques such as ELISA, PCR etc. 9 , 18 . The desired viral concentration is achieved by diluting the virus stock solution.…”
Section: Methodsmentioning
confidence: 99%
“…Some other HSV detection methods include immunofluorescence microscopy 14 , luciferase immunoprecipitation assay 15 , Tzanck smear 16 and electron microscopy 8 , 17 . Some of these immunoassay based tests, however, can have significant amounts of incorrect results 18 , 19 . It was previously reported that the sensitivity and specificity of enzyme based immunoassay techniques compared to culture was 65% and 93%, respectively 20 .…”
Section: Introductionmentioning
confidence: 99%